Standardization of Training Modules on Mushroom Cultivation Technology - Shirur, Mahantesh; Barh, Anupam; Annepu, Sudheer Kumar (Journal of Agricultural Extension Management, 2020)
The training programmes on mushroom cultivation technology in India are unidentical with a vague curriculum framework. This has overarching implications for the quality of training programmes on mushroom cultivation and subsequently on the mushroom enterprises in the country. The present study was undertaken to address this concern and standardize the curriculum framework and training modules on mushroom cultivation aspects. Eight training modules based on learning needs and training feedback of different stakeholders have been proposed. The curriculum development for all these training modules was done on the basis of relevancy analysis. The standardised training modules will serve as the quality benchmark for transactions in the learning environment. The proposed training modules will also serve for institutional policy formulation for training programmes on mushroom cultivation.